ROMANTISISME TEMBANG SUNDA CIANJURAN - R.M., Moch. Dava (LP2M ISBI Bandung, 2023)
Romanticism is an idea that prioritizes ideas, emotions, and feelings that are aesthetic and meaningful. Romanticism began in the 1790s and culminated in 1820s, romanticism is a complex movement that prioritizes emotions and feelings. Spontaneity movements do not rely on logic or reasonable opinions or reasons that underlie anything that has to do with romanticism. Inside Tembang sunda cianjuran, things that refer to the flow of romanticism can be easily found and even almost all of romanticism is a work that adheres to the flow of romanticism, . because in its presentation it is both in the lyrics and also in the way it feels. This Tembang sunda cianjuran prioritizes freedom of expression and also upholds feelings that are so emotional that in this case Tembang sunda cianjuran is a musical work that is Romanticism